Ovarian Vein Embolization With N-butyl-2 Cyanoacrylate Glubran-2® for the Treatment of Pelvic Venous Disorder - Gong, Maofeng; He, Xu; Zhao, Boxiang; Kong, Jie; Gu, Jianping; Su, Haobo (Frontiers in Surgery, 2021)
Background: There are few reports in the literature on the use of Glubran-2 for the embolization of ovarian veins in patients with pelvic venous disorder (PeVD), and a consensus on the efficacy and safety of Glubran-2 has not been reached. Purpose: To investigate the safety and efficacy of ovarian vein embolization (OVE) with N-butyl-2 cyanoacrylate (NBCA) Glubran-2 for the treatment of PeVD. Material and Methods: Between January 2013 and January 2020, 21 women (mean age, 43.9±13.3 y) with PeVD who underwent OVE with Glubran-2 were evaluated. Of those patients, ovarian vein or pelvic venous plexus insufficiency was verified by duplex ultrasound and/or multislice computer tomography (MSCT). The symptoms and signs of PeVD included chronic pelvic pain (CPP) (21/21; 100%), dyspareunia (12/21; 57.1%), dysmenorrhea (10/21; 47.6%), and vulvar varices (3/21; 14.3%). The medical data were retrospectively reviewed. Results: Glubran-2 was employed as the sole embolic material in 18 cases (85.7%) and used to perform rescue embolization in 3 cases (14.3%) due to CPP recurrence one month after initial embolization using microcoils. Technically successful embolization was achieved using Glubran-2 in all patients. No Glubran-2 related complications were noted. Neither persistent nor recurrent CPP was observed during follow-up, for which the mean was 62±38 months (range, 12-102 months). Clinical efficacy was evaluated, and all patients exhibited complete or slight improvement of CPP after embolization. The visual analog scale (VAS) score significantly decreased from preintervention to postintervention (p<0.001). Six patients (28.5%) gave birth to healthy babies during follow-up after embolization with Glubran-2. Conclusions: OVE with Glubran-2 is a feasible and safe treatment for CPP secondary to PeVD. This treatment may represent a potential and attractive alternative when patients desire symptom relief and want to continue reproducing. Larger studies are warranted to confirm the findings of this study.